1996
DOI: 10.1097/00004728-199603000-00032
|View full text |Cite
|
Sign up to set email alerts
|

Case Report. MRI of a Hibernoma

Abstract: Hibernomas are benign tumors derived from brown fat that most often present as painless, slowly enlarging masses in the interscapular region. Because these lesions have a heterogeneous appearance and contain fat, they mimic liposarcomas on CT and MR, requiring biopsy for definitive diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 5 publications
1
17
0
1
Order By: Relevance
“…The present 2 cases demonstrate that, in addition to malignant softtissue tumors, hibernoma is to be considered in the differential diagnosis in the case of increased vascularization. The presence of vascular channels on color Doppler sonography in a case of hibernoma has also been reported by Cook et al 1 Cross-sectional imaging studies (CT or MRI) are needed for preoperative planning. 2 The hypervascularization of the tumor explains the heterogeneous contrast enhancement seen on CT and MRI in most cases.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…The present 2 cases demonstrate that, in addition to malignant softtissue tumors, hibernoma is to be considered in the differential diagnosis in the case of increased vascularization. The presence of vascular channels on color Doppler sonography in a case of hibernoma has also been reported by Cook et al 1 Cross-sectional imaging studies (CT or MRI) are needed for preoperative planning. 2 The hypervascularization of the tumor explains the heterogeneous contrast enhancement seen on CT and MRI in most cases.…”
Section: Discussionsupporting
confidence: 56%
“…In contrast to lipomas, however the overlying skin can be warmer due to the rich vascularization of the tumor. 1 As a first diagnostic step for a palpable softtissue tumor, sonography is recommended. Grayscale images usually cannot distinguish reliably a lipoma, hibernoma, or low-grade liposarcoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, prominent branching and serpentine structures (low signal intensity with all MR pulse sequences) are often seen with contrast enhancement. [11][12][13][14][15] In our case, a dynamic-contrast MRI study showed branching and serpentine structures with early contrast enhancement. Although these features may initially suggest well-differentiated liposarcoma, this type of vascularity is not prominent in liposarcomas and may be an important feature for differentiation.…”
Section: Discussionmentioning
confidence: 94%